Did you see Chip? - Yee, Wong Herbert; Ovresat, Laura (Orlando : Harcourt, 2004)
After moving to the city, Kim makes some new friends while looking for her lost dog, Chip.
Accelerated Reader AR
Keywords: Dogs -- Fiction; Moving, Household -- Fiction; Lost and found possessions -- Fiction; Friendship -- Fiction; City and town life -- Fiction